ESCMID2 and ECMM3 joint clinical guidelines for the diagnosis and management of mucormycosis 2013. (April 2014) - Cornely, O. A.; Arikan‐Akdagli, S.; Dannaoui, E.; Groll, A. H.; Lagrou, K.; Chakrabarti, A.; Lanternier, F.; Pagano, L.; Skiada, A.; Akova, M.; Arendrup, M. C.; Boekhout, T.; et al.
Abstract: These European Society for Clinical Microbiology and Infectious Diseases and European Confederation of Medical Mycology Joint Clinical Guidelines focus on the diagnosis and management of mucormycosis. Only a few of the numerous recommendations can be summarized here. To diagnose mucormycosis, direct microscopy preferably using optical brighteners, histopathology and culture are strongly recommended. Pathogen identification to species level by molecular methods and susceptibility testing are strongly recommended to establish epidemiological knowledge. The recommendation for guiding treatment based on MICs is supported only marginally. Imaging is strongly recommended to determine the extent of disease. To differentiate mucormycosis from aspergillosis in haematological malignancy and stem cell transplantation recipients, identification of the reverse halo sign on computed tomography is advised with moderate strength. For adults and children we strongly recommend surgical debridement in addition to immediate first‐line antifungal treatment with liposomal or lipid‐complex amphotericin B with a minimum dose of 5 mg/kg/day. Amphotericin B deoxycholate is better avoided because of severe adverse effects. For salvage treatment we strongly recommend posaconazole 4 × 200 mg/day. Reversal of predisposing conditions is strongly recommended, i.e. using granulocyte colony‐stimulating factor in haematological patients with ongoing neutropenia, controlling hyperglycaemia and ketoacidosis in diabetic patients, and limiting glucocorticosteroids to the minimum dose required. We recommend against using deferasirox in haematological patients outside clinical trials, and marginally support a recommendation for deferasirox in diabetic patients. Hyperbaric oxygen is supported with marginal strength only. Finally, we strongly recommend continuing treatment until complete response demonstrated on imaging and permanent reversal of predisposing factors.